Poświęcenie, powołanie i cud w narracjach młodych katolickich matek o własnym macierzyństwie - Mętel, Dagmara; Krotofil, Joanna; Wójciak, Dorota (Kultura-Społeczeństwo-Edukacja, 2025)
Narrative plays a key role in understanding and communicating individual experiences, as well as in the process of identity formation. The transition to motherhood is often seen as a crisis that requires the creation of a new identity. The traditional Catholic narrative, together with the enduring matka Polka (Polish mother) myth in the Polish socio-cultural context, promotes an image of motherhood as a woman’s “vocation” and as a role defined by self-sacrifice and complete devotion to the child. Alongside these historically and culturally rooted models, alternative models have also emerged. Faced with this multiplicity of social constructions and the erosion of the unequivocally positive image of motherhood, women reflexively engage with the traditional-religious model of mothering. The research presented in this paper, based on interviews with young women who identify as devout Catholics, demonstrates that three key concepts in the religious narrative – sacrifice, vocation, and miracle – remain significant for mothers as they seek to make sense of their experiences and construct their identities as women and mothers. However, the meanings of these concepts are being renegotiated. Young Catholic women neither wholly reject nor uncritically reproduce religious idioms. Instead of passively replicating models that conflict with contemporary culture’s emphasis on individuality and freedom, they actively transform religious ideas, confronting them with their everyday lives. Through this process, they create narratives in which motherhood becomes a self-project grounded in individual choice while also remaining a religiously sanctioned aspect of their identity as women.